2014
DOI: 10.1111/jace.12939
|View full text |Cite
|
Sign up to set email alerts
|

Phase Structure and Property Evaluation of (Ba,Ca)(Ti,Sn)O3 Sintered with Li2CO3 Addition at Low Temperature

Abstract: A series of Li 2 CO 3 -added (Ba 0.95 Ca 0.05 )(Ti 0.90 Sn 0.10 )O 3 (BCTS) ceramics were prepared by normal sintering at a low temperature of 1300°C; Their microstructure and electrical property evaluation were investigated with special emphases on the effect of Li 2 CO 3 addition. Adding Li 2 CO 3 significantly improves the sinterability of BCTS ceramics, resulting in a reduced sintering temperature by more than 150°C. The coexistence of R and T phases is confirmed by the Raman spectrum at room temperature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…37 Table II shows a comparisons of our work with other reports. 19,20,23 The BCTSH + 2 Mn ceramics in our work have the lowest sintering temperature T S , the highest Curie temperature T C , high temperature stability, and good k p and Q m values.…”
Section: -12mentioning
confidence: 67%
“…37 Table II shows a comparisons of our work with other reports. 19,20,23 The BCTSH + 2 Mn ceramics in our work have the lowest sintering temperature T S , the highest Curie temperature T C , high temperature stability, and good k p and Q m values.…”
Section: -12mentioning
confidence: 67%
“…Meanwhile all the diffraction peaks of the matrix phase shifted to higher degree with increasing x . According to the Bragg's equation, the shift of the peak toward high angle indicated the shrinkage of the lattice parameters . So it could be deduced that the Al 3+ ions entered into the matrix, although it was not clear that the specific ions position where the Al 3+ ions occupied from the XRD patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Zhu et al [24] and other authors [25,26,27] have recently reported that the (Ba,Ca)(Ti,Sn)O 3 ceramics with high d 33 values are promising candidates for lead-free piezoelectric ceramics. However, it is not easy to find balance between lowering the sintering temperature and maintaining good piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal sintering promoter should effectively lower the sintering temperature while maintaining the piezoelectric properties as best as possible. In [26,27], Zhou and Zhao et al used CuO and Li 2 CO 3 as the sintering promoters to improve the piezoelectric and dielectric characteristics. The optimum d 33 values was improved from about 140 pC/N (pure BCTS) to an ultrahigh value of 683 pC/N for (Ba 0.95 Ca 0.05 )(Ti 0.93 Sn 0.07 )O 3 (BCTS)–CuO X and 485 pC/N for BCTS-Li 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%